Gatekept: Inviting Creative Community Literacy - Shelly Sanders; B. Cole Bennett (Journal of the Assembly for Expanded Perspectives on Learning, 2012)
Creative writing becomes a vehicle for community outreach in a Writing Center setting, bringing together town and gown.